2020
DOI: 10.3892/or.2020.7746
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK9: A novel biomarker in�the�treatment of endometrial cancer

Abstract: Endometrial cancer is one of the three major malignant tumors of the female reproductive system. Although cyclin-dependent kinase 9 (CDK9) has a definitive pathogenic role in various types of cancer, little is known concerning its function in endometrial cancer. Our study was conducted to evaluate the expression and therapeutic potential of CDK9 in endometrial cancer. CDK9 expression was determined by immunohistochemistry in endometrial cancer tissues constructed with paired primary, metastatic, and recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Treating cells with 10 µM ganciclovir (GCV) showed no effect in resolving HCMV inhibition of migration compared with infected untreated cells ( p = 0.999). Treating cells with 0.5 µM THAL-SNS032 almost completely abolished trophoblast migration consistent with the importance of CDK9 in cell migration [ 36 , 37 , 38 ]. Immunofluorescence analysis showed that there was no significant difference in levels of the HCMV immediate early protein expression between the treatment groups 24 h p.i.…”
Section: Resultssupporting
confidence: 56%
“…Treating cells with 10 µM ganciclovir (GCV) showed no effect in resolving HCMV inhibition of migration compared with infected untreated cells ( p = 0.999). Treating cells with 0.5 µM THAL-SNS032 almost completely abolished trophoblast migration consistent with the importance of CDK9 in cell migration [ 36 , 37 , 38 ]. Immunofluorescence analysis showed that there was no significant difference in levels of the HCMV immediate early protein expression between the treatment groups 24 h p.i.…”
Section: Resultssupporting
confidence: 56%
“…CDK9 expression had been implicated in the prognosis and resistance to anti-cancer therapeutics in a large number of cancer types like those of breast, lung, prostate, endometrium, apart from melanoma, osteosarcoma, myeloid leukemia, soft tissue sarcomas etc. [ 1 , 88 , 89 , 90 , 91 , 92 ]. We will briefly explain some of these cancer entities here.…”
Section: The Clinical Relevance Of Cdk9mentioning
confidence: 99%
“…Concentration dependent knock-down of CDK9 expression and dose-dependent inhibition of CDK9 activity by LDC000067 led to correspondingly significant reductions in cell viability and MCL-1 expression while BAX expression and PARP cleavage were enhanced. Additionally, 14 days of treatment with increasing concentrations of LDC000067 resulted in significant reductions of clonogenicity and 2D migration of endometrial cancer cell lines [ 90 ].…”
Section: The Clinical Relevance Of Cdk9mentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that transcriptional programs are highly dysregulated in cancers and that cancers become over-dependent on certain factors that control gene expression has led to increased efforts to inhibit transcriptional CDKs, such as CDK9 [ 21 ]. Preclinical studies in several cancer types, including osteosarcoma, synovial sarcoma, endometrial cancer, and leukemia, have focused on targeting CDK9 due to its role in controlling transcription of super-enhancer driven oncogenes such as MYC and anti-apoptotic proteins such as myeloid-cell leukemia 1 (MCL-1), which maintain cancer cell survival [ 22 , 23 , 24 , 25 , 26 ]. Clinically, it has been observed that CDK9 is overexpressed in many cancer types, such as pancreatic cancer, osteosarcoma, synovial sarcoma, and endometrial cancer [ 23 , 24 , 25 , 27 , 28 ], and that a high CDK9 expression correlates with poor patient prognosis [ 23 , 24 , 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%